Terahertz emission from vertically aligned InN nanorod arrays - Ahn, H.; Ku, Y.-P.; Wang, Y.-C.; Chuang, C.-H.; Gwo, S.; Pan, Ci-Ling (My University, 2007)
Terahertz emission from indium nitride (InN) nanorods and InN film grown by molecular-beam epitaxy on Si(111) substrates has been investigated. Terahertz emission from InN nanorods is at least three times more intense than that from InN film and depends strongly on the size distribution of the nanorods. Surface electron accumulation at the InN nanorods effectively screens out the photo-Dember field in the accumulation layer formed under the surface. The nanorods with considerably large diameter than the thickness of accumulation layer are found to be dominant in the emission of terahertz radiation from InN nanorod arrays. (c) 2007 American Institute of Physics.